Bone of the bone : essays on America by a daughter of the working class, 2013-2024 - Smarsh, Sarah (Scribner, an imprint of Simon & Schuster, LLC, 2024)
In Bone of the Bone, Sarah Smarsh brings her graceful storytelling and incisive critique to the challenges that define our times--class division, political fissures, gender inequality, environmental crisis, media bias, the rural-urban gulf. Smarsh, a journalist who grew up on a wheat farm in Kansas and was the first in her family to graduate from college, has long focused on cultural dissonance that many in her industry neglected until recently. Now, this thought-provoking collection of more than thirty of her highly relevant, previously published essays from the past decade (2013-2024)--ranging from personal narratives to news commentary--demonstrates a life and a career steeped in the issues that affect our collective future. Compiling Smarsh's reportage and more poetic reflections, Bone of the Bone is a singular work covering one of the most tumultuous decades in civic life. Timely, filled with perspective-shifting observations, and a pleasure to read, Sarah Smarsh's essays--on topics as varied as the socioeconomic significance of dentistry, laws criminalizing poverty, fallacies of the "red vs. blue" political framework, working as a Hooters Girl, and much more--are an important addition to any discussion on contemporary America. --